Single layer graphene protective layer on GaAs photocathodes for spin-polarized electron source - Jyoti Biswas; Mengjia Gaowei; Kali Prasanna Mondal; Erdong Wang; Jerzy T. Sadowski; Abdullah Al-Mahboob; Xiao Tong (APL Materials)
GaAs-based photocathodes are the primary choice for polarized electron sources, commonly used in polarized electron microscopes and polarized positron sources. GaAs photocathodes are typically activated with cesium and oxygen, which are highly reactive and require an ultra-high vacuum (∼10−11 Torr or lower) to operate reliably, resulting in substantial operational difficulties. A short exposure to a mediocre vacuum results in an instantaneous loss of cathode quantum efficiency (QE) due to the chemical reaction of the active layer with residual gas molecules or back-bombardment ions during operation. Covering the GaAs cathode with a 2D material, such as monolayer graphene, could provide protection against such damage due to the inhibition of chemical reactions with residual gas molecules. In this paper, we have incorporated a method known as intercalation to pass the active material underneath the graphene and activate the superlattice GaAs/GaAsP (SL-GaAs) photocathode. X-ray photoelectron spectroscopy, low-energy electron microscopy, and Mott scattering measurements were performed to evaluate the formation of the photocathode under graphene, as well as its spectral response and electron spin polarization. Our results demonstrate that the successful activation of the SL-GaAs photocathode with a graphene protection layer is achieved with a moderate QE. Furthermore, we found that the electron spin polarization of the cathode with a surface protection layer is higher than the conventional cathode without a protection layer.